Multilingual Legal Text Authentication and Harmonization of Legal Terminology: Foreign Models and Prospects for Kazakhstan - Kussainova А.К.; Omarova А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In the context of Kazakhstan’s integration into the international legal framework, the issue of ensuring linguistic authenticity of bilingual legal texts—officially published in Kazakh and Russian—gains particular importance. Discrepancies in meaning between the two language versions can negatively impact legal certainty, judicial consistency, and public trust in law. This study aims to comprehensively examine foreign models of legal text authentication and terminology harmonization and assess their applicability to Kazakhstan’s legislative process. Special focus is given to systems in Canada, Switzerland, Belgium, the EU and CIS countries. The relevance of this topic lies in addressing the institutional and linguistic barriers that hinder full equality between Kazakh and Russian in criminal law. The practical significance of the work is reflected in its development of specific proposals to improve Kazakhstan’s bilingual lawmaking, based on international standards. The research methodology is grounded in comparative legal analysis, examination of constitutional and sectoral acts, judicial practice, and academic literature. The study identifies effective institutional mechanisms and terminological strategies that support authenticity. It highlights the need for simultaneous bilingual drafting and enhanced linguistic review of legislative texts. A set of best practices and adaptation mechanisms for Kazakhstan is proposed. This research contributes to improving legal language quality and advancing the field of legal linguistics in Kazakhstan. The outcomes can be applied to prevent legal uncertainty arising from linguistic mismatches in legislation and to ensure equal interpretability of laws in both state languages.